Government ideology, economic pressure and risk privatization how economic worldviews shape social policy choices in times of crisis - Horn, Alexander ca. 20./21. Jh (Amsterdam University Press, 2017)
From the 1980s on, a privatization of labor market-related risks has occurred in the OECD. Governments have cut the generosity of social programs and tightened eligibility rules, particularly for the unemployed. Government Ideology, Economic Pressure, and Risk Privatization: How Economic Worldviews Shape Social Policy Choices in Times of Crisis analyses these curtailments for eighteen countries over the course of four decades and provides an encompassing comparative assessment of the interactive impact of government ideology and economic pressure. It demonstrates that the economic worldviews of governments are the most important factor in explaining why cuts are implemented or not. While ideas of non-intervention in the market underlie cuts in generosity, ideas of equality and fairness are at the heart of stricter eligibility criteria. This book also shows that the impact of the economic pressures often held responsible for the marginalization of politics and government ideology is in fact conditional on the specific ideological configuration
Title from publisher's bibliographic system (viewed on 23 Jun 2021)
Keywords: Social policy / Economic aspects; Right and left (Political science); Government spending policy / OECD countries; Ideology / OECD countries; Social problems / History; Privatisierung; Kürzung; Wohlfahrtsstaat; OECD countries / Social policy; OECD countries / Economic policy; Hochschulschrift